Behavioral Fatigue: Real Phenomenon, Naïve Construct, or Policy Contrivance? - Harvey, Nigel (Frontiers in Psychology, 2020)
In some countries, government policies to combat Covid-19 have been based on the notion that behavioural fatigue prevents people maintaining self-isolation and other restrictions to their life styles for more than a short time. By 16 March 2020, 681 UK behavioural scientists had signed an open letter to their government asking it to reveal the evidence that shows that behavioural fatigue exists. Nothing was forthcoming. The provenance of concept remains a mystery but modellers have argued that the delay in implementing lockdown policies, for which it was at least partly responsible, led to the loss of at least 20,000 lives. Here I consider whether behavioural fatigue is a real phenomenon by assessing a) direct evidence consistent and inconsistent with its existence, and b) indirect evidence drawn from other domains. I conclude that evidence for it is not sufficient to constrain policy. It is reasonable to conclude that behavioural fatigue is either a naïve construct or a myth that arose during the development of policy designed to tackle the Covid-19 crisis.